Digital Health Care and the Fourth Industrial Revolution. Issue 3 (July 2019) - Jung, Minsoo
Abstract : We live in a world where big medical data are being compiled. Many people make use of biometric information gathered by a variety of health care devices linked to smartphones, such as Fitbit devices. In addition, the development of medical information management schemes and the introduction of health information systems have greatly increased the possibility of using medical records stored in medical institutions. With the development of sensor technology and analytical capabilities, we have gained new knowledge through big data, stemming from the collection of data that was not important in the current medical area. Digital health care is moving toward creating value while creating utility as well based on data collected beyond the level of those collected by sensors. Only organizations that have quickly entered the market and accumulated data and have already developed advanced algorithms based on the data can be competitive. However, digital health care companies that survive in the market will lead the change and will reorganize the health care sector. In addition, a big data–based health care platform can help increase the number of e-patients through patient participation.